Dívida pública afeta variáveis reais? Um teste alternativo da equivalência Ricardiana por meio de testes de superexogeneidade em séries simuladas - Adolfo Sachsida; Fabio Nogueira Carlucci (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– This study suggests an alternative approach, nested in exogeneity tests, to verify Ricardian Equivalence. The intuitive appeal and the sophisticated statistical method are the advantage of this new procedure. Furthermore, two others contributions are made: a) an explanation to the failure of Ricardian Equivalence tests over the consumption function, as suggested by Kormendi (1983); and b) it is argued against the use of the value of the correlation parameter to infer about Ricardian Equivalence.
Keywords: H30; E62; C22; 330